Analysis of the Influence of Perceived Risk in E-commerce on Online Purchase Intention in Batam City Communities - Suprapto, Yandi; Wijaya, Prayogo Agung (Indonesian Journal of Economics, Social, and Humanities, 2023)
This study was conducted to determine the effect of perceived risk on online purchase intention in Batam city by purchasing goods through marketplace platforms such as: Tokopedia, Shoppe, Lazada, Bukalapak, Blibli. The technique of collecting data is carried out using non-probability sampling with judgmental sampling method. The respondent's data were collected as many as 320 data by distributing questionnaires to the Batam city community. Samples in this study were the Batam city people who had purchased goods or visited 5 marketplaces namely Tokopedia, Shoppe, Lazada, Bukalapak, Blibli. After collecting data in accordance with the required data, the data processing is carried out in the next stage to determine the results of this study using SPSS software. The results of the data testing conducted, it can be concluded that the financial risk, time risk, and psychological risk variables have a significant effect on the online purchase intention variable. Meanwhile, the variable product risk, security risk, and social risk do not have a significant effect on online purchase intention.